2016
DOI: 10.4081/ripppo.2016.198
|View full text |Cite
|
Sign up to set email alerts
|

The Lausanne Trilogue Play within the outcome evaluation in infant mental health: a preliminary report

Abstract: This study aims to contribute to the scientific debate about the evaluation of the intervention in infant mental health and presents the main results after one year of intervention based on integrated types of treatments (psychodynamic psychotherapy for the child/adolescent, parental support and observation and assessment of family interactions). Furthermore, the study aims to explore the use of the Lausanne Trilogue Play (LTP) as a new assessment tool for planning the of treatments. The sample consists of 23 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 27 publications
1
18
1
Order By: Relevance
“…A recent observational study was published which reported on the outcomes of 23 children and adolescents, who received weekly psychodynamic psychotherapy, and their parents received fortnightly support sessions alongside their child's therapy (Gatta, Sisti, Sudati, Miscioscia, & Simonelli, 2016). After one year of treatment, a statistically significant reduction in internalizing symptoms was found.…”
Section: Mixed Diagnosesmentioning
confidence: 99%
“…A recent observational study was published which reported on the outcomes of 23 children and adolescents, who received weekly psychodynamic psychotherapy, and their parents received fortnightly support sessions alongside their child's therapy (Gatta, Sisti, Sudati, Miscioscia, & Simonelli, 2016). After one year of treatment, a statistically significant reduction in internalizing symptoms was found.…”
Section: Mixed Diagnosesmentioning
confidence: 99%
“…The present project (approved by the local ethical committee-CEP 204 SC) was based on the above-mentioned premises, giving important consideration to the family household during the process of a patient's referral into the Service. The therapeutic approach involving the parents in the treatment considers the family as a structured subsystem and a composite set of different functions and roles, amongst which the roles of parenting, co-parenting, etc (35,36).…”
Section: Aimsmentioning
confidence: 99%
“…Nevertheless a recent study (Gatta et al, 2016b), aiming to examine the usefulness of the LTP as an outcome measure, found that the LTP assessment of the family interactions might help clinicians to focus on the dysfunctional familial dynamics, thus improving the effectiveness of a video-feedback intervention with the families of children and adolescents with psychiatric disorders (i.e., significantly reducing internalizing symptoms).…”
Section: Introductionmentioning
confidence: 99%